2018
DOI: 10.1016/j.micpath.2018.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of methicillin-susceptible Staphylococcus aureus (MSSA) isolated from milk of cows with subclinical mastitis

Abstract: Bovine mastitis has been a concern for dairy herd for decades. The adaptation capacity of one of the main species responsible for this disease, Staphylococcus aureus (S. aureus), plays a pivotal role in this issue. The aim of this study was to establish a molecular and phenotypic profile of 285 S. aureus strains isolated from milk of subclinical mastitis cows from 18 different farms in São Paulo State using spa typing, multilocus sequence typing (MLST), pulsed field gel electrophoresis (PFGE), agr cluster (I, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 49 publications
4
35
1
5
Order By: Relevance
“…A recent report from South America, performed in Sao Paulo, Brasil, examined more than 2,000 milk samples of bovine mastitis and 285 S. aureus strains, searching for the same enterotoxin genes than we did. The researchers found that the most frequently identified gene was seg, followed by seh 21 .These findings agree with reports on the presence of S. aureus enterotoxins in isolates from foods of different regions of the world. In Ethiopia, 51% of 160 S. aureus examined isolates from dairy products carried ET coding genes, being seg and sei the most frequently found, as in our series 22 .…”
Section: Discussionsupporting
confidence: 87%
“…A recent report from South America, performed in Sao Paulo, Brasil, examined more than 2,000 milk samples of bovine mastitis and 285 S. aureus strains, searching for the same enterotoxin genes than we did. The researchers found that the most frequently identified gene was seg, followed by seh 21 .These findings agree with reports on the presence of S. aureus enterotoxins in isolates from foods of different regions of the world. In Ethiopia, 51% of 160 S. aureus examined isolates from dairy products carried ET coding genes, being seg and sei the most frequently found, as in our series 22 .…”
Section: Discussionsupporting
confidence: 87%
“…Susceptibility to the majority or all antimicrobial agents tested against S. aureus isolates from bovine mastitis has been observed in Brazilian herds [90][91][92][99][100][101]. However, resistance frequencies have increased for some antimicrobial agents compared to studies published in earlier periods [102][103][104][105].…”
Section: Staphylococcus Aureus and Other Staphylococcus Sppmentioning
confidence: 99%
“…Beta-lactam resistance, especially to penicillinase-labile penicillins (PSLP; for example, amoxicillin, ampicillin, penicillin G), has been widely observed among Staphylococcus isolates recovered from bovine mastitis [91,[97][98][99][100][106][107][108]. Penicillin G resistance frequencies have ranged from 30.4% to 100% in the studies published in the last ten years [100,101,109,110]. Some studies have also tested other PSLPs, sometimes with slightly higher resistance frequencies than penicillin G [106,[111][112][113].…”
Section: Staphylococcus Aureus and Other Staphylococcus Sppmentioning
confidence: 99%
See 2 more Smart Citations